2003
DOI: 10.1046/j.1365-2982.2003.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Central tumour necrosis factor‐α mediates the early gastrointestinal motor disturbances induced by lipopolysaccharide in sheep

Abstract: Cytokines are involved in fever and other symptoms of the acute phase response induced by endotoxins. The aim of this work was to study the involvement of central tumour necrosis factor-alpha (TNF-alpha) in the changes induced by lipopolysaccharide (LPS) on gastrointestinal (GI) motility in sheep. Body temperature and myoelectric activity of the antrum, duodenum and jejunum was recorded continuously. Intravenous (i.v.) administration of LPS (0.1 micro g kg-1)-induced hyperthermia, decreased gastrointestinal my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Mucosal inflammation activates leukocytes in the gastric wall, which release immunoregulatory cytokines such as interleukin (IL)-1, IL-6, IL-8, and tumor necrosis factor (TNF)-α [28][29][30][31], while nitric oxide (NO) production also increases due to induction of NO synthase [32]. Some of these cytokines are known to interfere with gastrointestinal motility [33][34][35][36], while NO inhibits gastric emptying and antral motility [37]. Therefore, cytokines and NO or other inflammatory mediators released from the injured gastric wall may disturb gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal inflammation activates leukocytes in the gastric wall, which release immunoregulatory cytokines such as interleukin (IL)-1, IL-6, IL-8, and tumor necrosis factor (TNF)-α [28][29][30][31], while nitric oxide (NO) production also increases due to induction of NO synthase [32]. Some of these cytokines are known to interfere with gastrointestinal motility [33][34][35][36], while NO inhibits gastric emptying and antral motility [37]. Therefore, cytokines and NO or other inflammatory mediators released from the injured gastric wall may disturb gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of TLR4 leads to an activation of the nuclear factor-κB (NF-κB), stimulating the synthesis of pro-inflammatory cytokines [18]. TNFα is known to inhibit smooth muscle contractions [19] and is capable of inhibiting gastrointestinal motility when injected centrally [20]. It was shown that TNFα binding protein protects animals from LPS induced intestinal dysmotility [21].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of TNFα on gastrointestinal motility is not completely understood. As mentioned above, circulating TNFα is capable of inhibiting both smooth muscle activity in the gut and central neural pathways regulating gastrointestinal motility by passing the blood brain barrier [20,24,25]. However, it is also possible that TNFα itself plays a minor role in inhibiting gastrointestinal motility, as it instead stimulates other cells releasing mediators which inhibit gastrointestinal motility.…”
mentioning
confidence: 99%
“…Experimental findings suggest the role of various cytokines and other mediators in gastrointestinal motility disturbances [14, 15]. Resident intestinal muscularis macrophages are rapidly activated after surgical injury and may be involved in inflammatory responses resulting in postoperative ileus [16].…”
Section: Discussionmentioning
confidence: 99%